Uma disciplina, uma história : cálculo na licenciatura em Matemática da Universidade Federal de Sergipe (1972-1990) - Oliveira, Fabiana Cristina Oliveira Silva de (2009)
The present work has the intention to construct a history of discipline Calculation in the course of Degree in Mathematics of the Federal University of Sergipe, during the period from 1972 to 1990. It examines the historical curse of discipline by means of the workload, of the prerequisite ones, of its contents, its professors and methods of teaching. It analyzes the history of the Calculation in the prism of the history of the disciplines, taking as sources the lesson plans, minutes acts, resolutions, reports, didatic books and verbal stories. We infer that the changes pass the discipline Calculation had went in regards to the workload of great relevance; however, in if treating to prerequisite and summaries, the alterations were smaller. In the case of the movement of contents of each disciplines, we notice that in elapsing of the years the malter of teaching Calculation was configured gradually and before assuming its last formation it pass for different disciplines with reformularizations in its configuration, with distinct signatures, with distinct workload, but with the same contents. We observed although there was renewal of the teaching picture causing significant alterations regarding the profile of the professors of Calculation. We consideed that the method of the lesson was closely connected to the use that the theacher could make of the book and the applications of exercises.